Analisis Beban Kerja dan Jumlah Karyawan yang Optimal Berdasarkan Pemetaan Proses Bisnis di Restoran Sedjagad 36 - Nohos, Margaretha Wulandari (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study analyzes the mental and physical workload of employees at Sedjagad36 Restaurant using the NASA-TLX and Cardiovascular Load (CVL) methods. Fourteen employees from barista, kitchen, and waiter divisions participated in the study. The results show that 42.9% of employees experience a high mental workload, while 57.1% fall under the moderate category. Temporal Demand and Effort are the most dominant indicators, indicating pressure from time constraints and exertion. Physical workload measured through CVL falls into the light category, yet it increases significantly during weekends due to higher customer volume. Observational findings also show that operational SOPs and long shifts contribute to both mental and physical workloads. Recommendations include shift adjustments, job rotation, and workload management improvements to reduce fatigue.